Species Diversity of Lichens in the Province of Abra, Philippines - Guzman, Mary Joan T.; Fabito, Robinson Q. (JPAIR Multidisciplinary Research, 2016)
The province of Abra is rich in natural resources. Environmental sustainability has been one of the advocacies to sustain enough resources to meet our needs. The study was conducted to determine the species diversity of lichens in the province of Abra, Philippines. Specifically, the study documented the species of lichens found in the study sites. The taxonomic classification of the lichen species was documented and identified using the Dichotomous Key for Lichens. Samples of lichens were collected by scraping them from the substrate. Results revealed that Abra could be a rich culture ground for lichens. From 10,659 collected individuals of lichens, 44 species came out. Parmtotremarubifaciens lichen appeared to have potential medicinal properties since phytosterol, phenolic compounds, and flavonoid were positive within it. Crustose type of lichens was the most abundant type having 25 species. Of all the 44 species of lichens, there were five species commonly found in all the 27 study sites. Lichens and their natural habitats should not be destroyed by logging, and the use of toxic chemicals that could contaminate the air should be avoided as well as burning of wastes.
Keywords: Botany; Lichens; descriptive design; Abra; Philippines